Integrating Levels of Hierarchical Organization in Porous Organic Molecular Materials - Ferrando‑Soria, Jesus; Fernandez, Antonio (Nano-Micro Letters, 2024)
Porous organic molecular materials (POMMs) are an emergent class of molecular-based materials characterized by the formation of extended porous frameworks, mainly held by non-covalent interactions. POMMs represent a variety of chemical families, such as hydrogen-bonded organic frameworks, porous organic salts, porous organic cages, C − H⋅⋅⋅π microporous crystals, supramolecular organic frameworks, π-organic frameworks, halogen-bonded organic framework, and intrinsically porous molecular materials. In some porous materials such as zeolites and metal organic frameworks, the integration of multiscale has been adopted to build materials with multifunctionality and optimized properties. Therefore, considering the significant role of hierarchy in porous materials and the growing importance of POMMs in the realm of synthetic porous materials, we consider it appropriate to dedicate for the first time a critical review covering both topics. Herein, we will provide a summary of literature examples showcasing hierarchical POMMs, with a focus on their main synthetic approaches, applications, and the advantages brought forth by introducing hierarchy. Highlights: 1 This review covers the extent of the integration of hierarchy in porous organic molecular materials (POMMs) for the first time. 2 Three main hierarchies are identified in POMMs: composition, architecture, and porosity. 3 The synthesis and applications of hierarchical POMMs, while highlighting the advantages of having hierarchy, are discussed.